Analytical formulas for estimation of phase-averaged parameters of random waves. (15th March 2017) - Srisuwan, Chatchawin; Rattanamanee, Payom; Rattanapitikon, Winyu
Abstract: New analytical formulas for the estimation of wave radiation stress and wave mass flux are developed in this study based on asymptotic analysis of linear wave theory with the aid of non-directional parameterized wave spectra. Verification against synthetic wave data shows that the new formulas can allow up to 10% more accurate results compared to the use of the traditional representative wave approach. Sensitivity analysis based on reliable wave buoy data reveals that the performance of the new formulas may vary by up to 20% depending on the relative wave height, wave steepness, and spectral width. For a common sea state dominated by wind-induced waves, the formulas are most sensitive to the relative water depth kp h and their best applicable range is in upper transitional to deep water conditions ( k p h ≥ π / 2 ) . The formulas were finally validated against nine independent sets of field wave spectra to reassure their superiority over the representative wave approach. The validation confirms that the new formulas can offer up to 10% and 15% improvements in terms of the estimation accuracy and the estimation precision, respectively. Abstract : Highlights: New analytical formulas for estimation of mass flux and radiation stress of random waves. Accuracy and precision improving up to 10% and 15% compared to use of representative wave approach. Synthetic tests showing best applicability of the formulas in upper intermediate to deep water. Estimation capability varying up to 20% due to sensitivity on relative wave height, steepness, and spectral width. Tests with various field datasets confirming the capability and the applicability of the new formulas.